Models of emotional intelligence : a review - Pavitra Kanesan,; Norsiah Fauzan, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Models of emotional intelligence have been categorised into three models known as ability model, mixed model and trait model as Bar-On, Goleman and Petrides, Salovey and Mayer defined emotional intelligence differently. This paper reviews conceptualisations of emotional intelligence by analysing the goodness and weakness in the models of emotional intelligence. Generally, the existing models have described emotional intelligence as personal intelligence (understanding, managing and utilising emotion in oneself) and social intelligence (understanding and managing emotion in others). The review concludes that ability model is the best model to elaborate emotional intelligence phenomena as emotional intelligence is (1) viewed as intelligence, (2) founder of emotional intelligence proposed this model, (3) ability model fits well with the common definition, “managing emotion in oneself and in others”; (4) emphases pure form of emotional intelligence excluding personality trait compared to mixed and trait models.